The Effect of Time Variation and Number of Fiberglass Layers in the Composite Material Manufacturing Process on Tensile Strength, Bending and Surface Flatness: Pengaruh Variasi Waktu dan Jumlah Lapisan Fiberglass dalam Proses Pembuatan Material Komposit Terhadap Kekuatan Tarik, Tekuk dan Kerataan Permukaan - Mulyadi, Mulyadi; Dimas Sunu Purwohadi; Iswanto (Universitas Muhammadiyah Sidoarjo, 2025)
This research explores the production of fiberglass composite materials using an open mold process with pressing, aiming to overcome the uneven surfaces often produced by the hand lay-up method. Conducted in the Mechanical Engineering laboratories of Universitas Muhammadiyah Sidoarjo (UMSIDA) and Politeknik Negeri Malang, the study tested specimens using tensile testing (ASTM D638 Type I) and flexural testing (ASTM D790), along with surface flatness measurement via a dial indicator. The research varied the number of fiberglass layers (2, 3, and 4) and the pressing duration (3, 4, and 5 hours). Tensile tests showed the best stress and strain with 2 layers of fiberglass and 3 hours of pressing, with the